Literasi Ekonomi Guru: Kajian Berdasarkan Sosio-Demografi - Dwi Nurhayati; Neti Budiwati (FKIP Unswagati, 2020)
AbstractThe purpose of this study is to study and analyze the economic effects of high school teachers based on age, gender, and certification that can affect the level of economic literacy. The research method in this research is explanatory survey with hypothesis testing and data collection techniques through testing and questionnaires. The population of the study was 130 economic teachers consisting of 52 schools and a sample of 98 teachers consisting of 30 schools. The collected data is then analyzed using cross tabulation and multiple regression data analysis techniques. The results showed that the level of economic literacy in economics teachers was categorized high. It is known that age variables have the most influence on the economic literacy compared to other variables studied with a coefficient of 0.492. Then other variables that have an influence on the economic literacy are gender variables with a coefficient of 0.291 and sertification variables with a coefficient of 0.199. This finding implies that in order to improve the economic literacy, it is necessary to improve age, gender, and certification.Â Keywords: Economic literacy, Teachers.